(3GdcGaj aj fXe GdTGajs - (3eMehO Hf eMeO Hf GdYHGS Hf CQSdGf GdYHGSj GdNhGQRej GdTGaYj, XgjQ GdOjf CHh eMeO,J (B568 (3g` s
(3ChdgG (B:s
(3cJGH GdHjY GdHjY JUQa eTQhY s
(3BNQgG (B:s
(3Je GdLRA GdKGfi ef GdcGai ai GdfXe GdTGai jJdhg Ef TGA Gddg JYGdi GdLRA GdKGdK cJGH GdfcGM hGdMeO ddg QH GdYGdejfq s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B829 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B403s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs